The new world goblin spiders of the new genus Neotrops (Araneae: Oonopidae) Part I. - Grismado, Cristian José (2013)
A new genus of soft-bodied oonopids, Neotrops, is established for a large assemblage of goblin spiders found in all tropical and subtropical areas of the Neotropical region, from Panama to Uruguay and central Argentina. Members of Neotrops have spinose forelegs, and share a general palpal morphology with those of Heteroonops Dalmas, but have a prolateral conductor connected with an internal bulbal vesicle that presumably discharges its secretion through a prolateral slit. Females lack a posterior receptacle in the internal genitalia, having only a posterodorsal plate serving for muscle attachment. Here we treat all the species except those from Brazil, which will be addressed in a subsequent paper. Twenty-three new species are described: N. darwini (type species), N. lorenae, and N. sciosciae (from Argentina and Uruguay); N. yunga, N. piacentinii, N. poguazu, and N. lopardoae (from Argentina); N. rubioi, N. pombero, and N. avalosi (from Argentina and Paraguay); N. labarquei (from Uruguay), N. yabare, N. izquierdoi, and N. kopuchianae (from Bolivia); N. pithecia, N. silvae, and N. pakitza (from Peru); N. platnicki, and N. waorani (from Ecuador); N. santamarta and N. caparu (from Colombia); and N. maracay and N. amacuro (from Venezuela). Four additional species, previously placed in Oonops Templeton, are transferred here to Neotrops: O. nigromaculatus Mello-Leita˜o, from Argentina and Uruguay; O. tucumanus Simon, from Argentina; O. donaldi Chickering, from Panama; and O. trapellus Chickering, from Trinidad and Venezuela. The females of the three latter species are here described for the first time. Most of the species are known from the leaf litter or the foliage of tropical and subtropical forests, but also from grasslands in the southern parts of their distributional range, where they appear as the dominant soft-bodied oonopids. The relationships of this new taxon are briefly discussed, and intrageneric groupings are also proposed.